Positive conflict resolution behaviors in psychological health: Northern Cyprus sample - İsmail Hatun; NergÜz Bulut Serin (International Journal of Public Health Science (IJPHS), 2021)
Conflicts are an inevitable part of school life, as in all areas of life, and minimizing the negative effects of conflicts and trying to develop constructive conflict resolution skills will positively contribute to human relations and mental health. The aimed of this study was to investigate the conflict resolution behaviors of secondary school students in terms of some psycho-social variables. The sample of the study was 6th, 7th and 8th grade students attending the state secondary schools of the Turkish Republic of Northern Cyprus. The study was conducted with a total of 175 students of the students. The research was a descriptive study which is prepared by using quantitative research method which examines conflict resolution behaviors of secondary school students. The sample of the study was determined by non-random sampling method. In order to collect data, Conflict Resolution Behavior Determination Scale was used. In the analysis of the data; percentages, one-way analysis of variance (ANOVA), t-tests were used. As a result of the study, there was no significant difference according to the gender and grade level of the students. A significant difference was found according to their age, parental partnership status and success levels.